Influence of Diameter and Length of Implant on Early Dental Implant Failure - Olate, Sergio; Lyrio, Mariana Camilo Negreiros; de Moraes, Márcio; Mazzonetto, Renato; Moreira, Roger William Fernandes (Journal of oral and maxillofacial surgery, 2010)
To relate diameter and length of implants with early implant failure. Implants with a cylindrical design and surface treatment by removal of titanium via acidification from 3 different manufacturers were used in this study. Two surgical procedures for submerged implants were evaluated—the placement of the implants (first surgical phase) and the procedure for reopening (second surgical phase)—before the installation of the prosthetic system. The length of the implants was classified as short (6-9 mm), medium (10-12 mm), or long (13-18 mm), and the diameter was classified as narrow, regular, or wide. The statistics were computed with SAS statistical software (SAS Institute, Cary, NC). Step-wise and χ 2 analyses were used, in addition to univariate and multivariate logistic regression. In this retrospective study, 1,649 implants (807 maxillary and 821 mandibular) were placed in 650 patients (mean age, 42.7 years) in different areas: anterior maxilla (458), posterior maxilla (349), anterior mandible (270), and posterior mandible (551). The early survival rate for all 1,649 implants was 96.2%. Regarding diameter, the largest loss was observed in narrow implants (5.1%), followed by regular (3.8%) and wide (2.7%) implants. Regarding length, the largest loss was observed in short implants (9.9%), followed by long (3.4%) and medium (3.0%) implants. Early loss occurred in 50 implants, 31 (4.3%) of which were installed in anterior areas and 19 (2.8%) in posterior areas. According to step-wise analyses and the χ 2 test, short implant ( P = .0018) and anterior installation of implant ( P = .0013) showed associations with early loss. A significant relationship of early implant loss was observed with short implants. No relationships between early loss of implants and the osseous quality or diameter of implants were observed. These findings may be attributed to the operator's experience with different implant designs, learning curves, or changes in technique and indications for the use of short implants from 1996 to 2004.